Islam and Environmental Stewardship: Da'wah as a Viable Alternative - Muhammad Maga Sule; Salihi Ashiru Musa (Maddah: Journal of Advanced Da'wah Management Research, 2025)
This paper Islam and environmental stewardship: Da’wah as a vital solution examines the intersection of Islamic teachings and environmental stewardship, highlighting the critical role of Da’wah (propagating the message of Islam) in promoting sustainable practices and environmental responsibility. By examining Islamic principles and texts, this research demonstrates the importance of Da’wah in raising awareness, inspiring eco-friendly lifestyles, and fostering accountability. Da'wah is identified as a vital solution for raising environmental awareness, inspiring eco-friendly lifestyles, and fostering a sense of accountability among Muslims. The study argues that Islamic Da’wah can mobilize collective action, promote cooperation, and contribute to a global response to environmental challenges not only among the Muslims but can also encourage people of other religion. By embracing Islamic teachings, Muslims can play a significant role in addressing environmental issues and ensuring a sustainable future. The paper further argues that the concept of environmental stewardship as integrated in the global, regional and national environmental protection plans, movements and strategies, particularly as it relates to the Muslim Ummah. The paper presents a brief description of verses dealing with the environmental stewardship and explores into the eco-philosophy of Islam scriptures and the teachings. The study adopted desk review base research, hence data collected from secondary sources. The paper concludes with a number of important findings, such as the necessity for employing Da’wah approach in environmental protection in accordance with the purposes of and values of Islamic teachings.